Study of motion stability of a viscoelastic rod - Ірина Костюшко; Гліб Шаповалов (Mechanics and Advanced Technologies, 2024)
Stability of non-conservatively loaded elastic and inelastic bodies – a classic section of deformable solid mechanics that has been of interest for many years. In this paper, we study the motion stability of a free rod subjected to a constant tracking force on one of its ends. The defining ratio of the rod material is the Kelvin-Voigt model. The solution is presented in the form of an expansion in terms of beam functions. The number of terms of this expansion is substantiated. The values of the critical load in the presence and absence of viscosity are determined. The given analytical results are confirmed by numerical calculations.